A study of pathophysiological factors associated with gastro‐esophageal reflux disease in twins discordant for gastro‐esophageal reflux symptoms. Issue 8 (26th May 2013) - Iovino, P.; Mohammed, I.; Anggiansah, A.; Anggiansah, R.; Cherkas, L. F.; Spector, T. D.; Trudgill, N. J.
Abstract Background Differences in lower esophageal sphincter (LES) and peristaltic function and in transient LES relaxations (TLESR) have been described in patients with gastro‐esophageal reflux disease (GERD). However, some of these differences may be the result of chronic GERD rather than being an underlying contributory factor. Methods Twins discordant for GERD symptoms, i.e., only one twin had GERD symptoms, underwent standard LES and esophageal body manometry, and then using a sleeve sensor prolonged LES and pH monitoring, 30 min before and 60 min after a 250 mL 1200 kcal lipid meal. Key Results Eight monozygotic and 24 dizygotic female twins were studied. Although there was no difference in preprandial LES pressure (symptomatic 13.2 ± 7.1 mmHg vs asymptomatic 15.1 ± 6.2 mmHg, P = 0.4), LES pressure fell further postprandially in symptomatic twins (LES pressure area under the curve 465 ± 126 vs 331 ± 141 mmHg h, P < 0.01). 12/37 (32%) of acid reflux episodes in symptomatic twins occurred due to low LES pressure or deep inspiration/strain and 0/17 in asymptomatic twins (P = 0.01). There was no difference between symptomatic and asymptomatic twins in: peristaltic amplitude, ineffective esophageal body motility, hiatus hernia prevalence, or LES length. There was also no difference in TLESR frequency preprandially (symptomatic median 1(range 0–2) vs asymptomatic 0(0–2), P = 0.08) or postprandially (2.5(1–8) vs 3(1–6), P = 0.81). Conclusions & Inferences Twins with GERD symptoms had lower postprandial LES pressure and given the close genetic link between the twins, it is possible that such differences are caused by GERD. Acid reflux episodes associated with a hypotensive LES were seen in symptomatic, but not in asymptomatic twins.